Pesantren and Interfaith Dialogue - Muhammad Muntahibun Nafis (IAIN Ponorogo, 2022)
This research examines pesantren’s effort to develop the concept of religious moderation with interreligous dialogue. The pesantren are not static and conservative Islamic institutions. Ngalah Pesantren has developed effective and unique strategies to change religious behavior especially about religious moderation. In the Ngalah’s experience has both religious and formal education and invites some non-Muslimsto teach in the pesantren. It has become a center of inter-religous diologue. Ngalah offer a Model Theory of Architecture with a House Concept in interfaith dialogue in the style of Indonesian Islam-based on Panikkar's theory. The author tries to offer an additional theory of the five Panikkar theories related to interreligious dialogue. Ngalah promote inter-religious dialogue with Architecture model and home concept. This study contributes as the main study material related to the development of interfaith dialogue in pesantren and become the key data that pesantren’s are not a place for the growth of terrorism and radicalism.